The Vertebrate Claudin/PMP22/EMP22/MP20 family protein TMEM47 Regulates Epithelial Cell Junction Maturation and Morphogenesis - Dong, Yi (Dev Dyn, 2016)
BACKGROUND: TMEM47 is the vertebrate orthologue of C. elegans VAB-9, a tetraspan adherens junction protein in the PMP22/EMP/Claudin family of proteins. VAB-9 regulates cell morphology and adhesion in C. elegans and TMEM47 is expressed during kidney development and regulates the activity of Fyn. The conserved functions of VAB-9 and TMEM47 are not well understood. RESULTS: expression of TMEM47 in C.elegans functionally rescues vab-9 mutations. Unlike Claudins, expression of TMEM47 in L fibroblasts does not generate tight junction strands, instead, membrane localization requires E-cadherin expression. Temporally, TMEM47 localizes at cell junctions first with E-cadherin prior to ZO-1 co-localization and in polarized epithelia, TMEM47 co-localizes with adherens junction proteins. By immunoprecipitation, TMEM47 associates with classical adherens junction proteins, but also with tight junction proteins Par6B and aPKCλ. Over-expression of TMEM47 in MDCK cells decreases apical surface area, increases activated myosin light chain at cell-cell contacts, disrupts cell polarity and morphology, delays cell junction reassembly following calcium switch, and selectively interferes with tight junction assembly. Reduced TMEM47 expression results in opposite phenotypes. CONCLUSIONS: TMEM47 regulates the localization of a subset of tight junction proteins, associated actomyosin structures, cell morphology, and participates in developmental transitions from adherens to tight junctions.